A review on the Destitute Persons Act 1977 on beggars / Lily Umyra Norani ... [et al.] - Norani, Lily Umyra; Zambri, Nur Syazana; Abd Halim, Siti Atikah; Nasron, Nur Amirah (Faculty of Law, 2013)
In Malaysia, beggars are governed by the Destitute Persons Act 1977. Nonetheless as the researchers further researched, there are other provisions governing the beggars but however the effectiveness of the provisions is not yet proven. The research conducted has detected several loopholes and weaknesses where the provisions are insufficient in combating the beggars. The research also has taken into account the view from the law enforcers that deal with these beggars on the practicality of the law. The research also has look into other countries such as Singapore, India and Philippines, regarding their law on beggars. The research has come out with a result that these countries have better enforcement and regulation in governing the beggars. It is the intention of the researchers to review the Destitute Persons Act 1977 by suggesting method or ways from other countries, which may help in preventing the problefm of begging. The research has suggested some ways in curbing and also preventing the problem from arisen. Along with that the researchers have suggested an amendment should be made to the Destitute Persons Act 1977.